Nutritional Changes of Sour Cherry (Prunus cerasus) Kernel Subjected to Aspergillus niger Solid-state Fermentation - (:unkn) unknown (My University, 2017)
0

This study was carried out to investigate the effects of Aspergillus niger solid-state fermentation on main nutritional content of cherry (Prunus cerasus) kernel. Three Aspergillus niger strains (ATCC 52172, ATCC 200345, ATCC 9142) were used in this study. Cherry kernels were analyzed for crude protein (CP), total ash (TA), total fat (TF), crude fiber (CF), nitrogen free extract (NFE), neutral detergent fiber (NDF) and acid detergent fiber (ADF) before and after fermentation to see nutritional change. CP level of the sour cherry increased by 14.1% and reached up to 41.66% from 27.56%.Fungal fermentation changed also TA, TF, CF, NFE, NDF, ADF contents of cherry kernel. These results suggest that solid-state fermentation with Aspergillus niger can be used for utilization nutritional properties of cherry kernels to make having potential in animal nutrition.
Keywords: Ziraat Mühendisliği